Transcriptions of 12 interviews with SEN investigators and decision-makers in North Rhine-Westphalia, Germany - Barow, Thomas (University of Gothenburg, 2018)
The file contains transcriptions of 12 interviews with SEN investigators and decision-makers in North Rhine-Westphalia (NRW), Germany. Altogether the material includes about 14 h of tape recorded material (not saved) or 200 pages transcriptions. The interviews were conducted in five municipalities of the state NRW. Research questions were focusing on the thought styles of the interviewees.

Purpose:

The purpose of the study is to analyse the process of special education needs [SEN] assessment in North Rhine-Westphalia, Germany.

Filen innehåller transkriptioner av 12 intervjuer med utredare och beslutsfattare i pedagogiska utredningar i Nordrhein-Westfalen, Tyskland. Sammanlagt handlar det om ca 14 t bandupptagningar (inte sparade) eller 200 sidor material. Intervjuerna har genomförts i fem kommuner i delstaten. Frågeställningarna undersökte vilka framträdande tankestilar som finns hos de intervjuade.

Syfte:

Syftet med studien är att analysera pedagogiska utredningar i samband med kategoriseringen ”i behov av särskilt stöd” i Nordrhein-Westfalen, Tyskland.
Transkriptioner av 12 intervjuer med utredare och beslutsfattare beträffande det särskilda stödbehovet i Nordrhein-Westfalen, Tyskland - Transkriptioner av 12 intervjuer med utredare och beslutsfattare över det särskilda stödbehovet i Nordrhein-Westfalen, Tyskland
Keywords: teachers; lärare; educational tests; pedagogiska tester; schools; skolor; educational personnel; pedagogisk personal; school-student relationship; skola-elevförhållande; special education teachers; speciallärare; EDUCATION; UTBILDNING; Social Sciences; Samhällsvetenskap; Educational Sciences; Utbildningsvetenskap